Molybdenum Extraction from Spent Catalyst Using Citric Acid: Characteristic and Kinetics Study. Issue 1 (September 2021) - Rezki, Amelia Sri; Sumardi, Slamet; Astuti, Widi; Made Bendiyasa, I; Petrus, Himawan Tri Bayu Murti
Abstract: Interest on the extraction of valuable metals from secondary resources has been increasing recently due to the environmental consideration. It includes the spent catalyst from hydrodesulfurization process from the natural gas purification unit in fertilizer industry to reduce sulfur content. With composition of molybdenum as one of the active elements, the spent hydrodesulfurization (HDS) catalyst is indeed interesting to study, in order to be able to recover the molybdenum which is increasing within decades in need and unit price. In this study, recovery as well as extraction kinetics of molybdenum will be observed to calculate design parameters for scaling up process. The raw material used in this work is spent catalyst from PT. Pupuk Kujang Cikampek, Karawang, Indonesia. Leaching process was conducted with particle size -200 mesh, solid ratio of 1:5 and leaching time up to 120 minutes in the atmosphere condition by variated temperature (60, 80, 90°C) and pH (1.5, 2, 2.5) of citric acid. The solid samples before leached were analyzed using Energy Dispersive X-Ray (EDX), while the leaching filtrate samples were analyzed using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). The result of the experiment showed the maximum recovery of molybdenum at temperature of 90°C, during 120 minutes, and acid pH 1.5, 2, 2.5 were 71.20%, 34.66%, and 19.29% respectively. The independent variables used in this study showed a significant effect of molybdenum recovery, especially the acids pH. The kinetic model was evaluated by following the Shrinking Core model which considers diffusion is suitable to predict the leaching mechanism of molybdenum using citric acid.